2019
DOI: 10.1002/aid2.13112
|View full text |Cite
|
Sign up to set email alerts
|

Management of postendoscopic sphincterotomy bleeding with fully covered self‐expanding metal stent

Abstract: Postendoscopic sphincterotomy (ES) bleeding is one of the most frequent complications following ES. Different endoscopic interventions are available to manage post‐ES bleeding. Recently, the temporary placement of fully covered self‐expanding metal stent (FCSEMS) to achieve a tamponade effect has been described in post‐ES bleeding not controlled by other measures. The aim of this article is to present our clinical experience with management of post‐ES bleeding using FCSEMS. This is a retrospective analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…To our knowledge, this is the largest study reporting outcomes in patients treated with FCSEMS for EBS-related bleeding. Previous reports have described improved hemostasis rates with FCSEMS compared to other endoscopic interventions [20][21][22][23] While our study did not have a control arm, we observed durable hemostasis in the 94 % of patients undergoing FCSEMS. In addition, seven patients who were not managed with FCSEMS placement at the time of immediate EBS-related bleeding, were successfully managed with FCSEMS on subsequent ERCP.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…To our knowledge, this is the largest study reporting outcomes in patients treated with FCSEMS for EBS-related bleeding. Previous reports have described improved hemostasis rates with FCSEMS compared to other endoscopic interventions [20][21][22][23] While our study did not have a control arm, we observed durable hemostasis in the 94 % of patients undergoing FCSEMS. In addition, seven patients who were not managed with FCSEMS placement at the time of immediate EBS-related bleeding, were successfully managed with FCSEMS on subsequent ERCP.…”
Section: Discussionmentioning
confidence: 45%
“…Over the last decade, several series and small cohort studies have reported utilizing fully covered self-expanding metal stents (FCSEMS) to achieve hemostasis in severe cases of EBSrelated bleeding that were refractory to traditional management [18][19][20][21][22][23]. A recent retrospective study compared FCSEMS to traditional endoscopic modalities for the management of EBS-related bleeding after failure of traditional endoscopic modalities [20].…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al recently reported their own successful experience of treatment of post‐ES bleeding in Taiwan by using FCSEMS after failure of conventional endoscopic interventions within a 3‐year period. Immediate hemostasis was achieved in five of six patients except one, who needed an additional application of hemoclip to stop the bleeding.…”
mentioning
confidence: 99%